Real-time bandwidth encapsulation for IP/MPLS Protection Switching - Lubasi, Mampi Nakutoma (Department of Electrical Engineering, 2015)
Bandwidth reservation and bandwidth allocation are needed to guarantee the protection of voice traffic during network failure. Since voice calls have a time constraint of 50 ms within which the traffic must be recovered, a real-time bandwidth management scheme is required. Such bandwidth allocation scheme that prioritizes voice traffic will ensure that the voice traffic is guaranteed the necessary bandwidth during the network failure. Additionally, a mechanism is also required to provide the bandwidth to voice traffic when the reserved bandwidth is insufficient to accommodate voice traffic. This mechanism must be able to utilise the working bandwidth or bandwidth reserved for lower priority applications and allocate it to the voice traffic when a network failure occurs.